A new socially parasitic Braunsapis (Hymenoptera: Apidae: Xylocopinae: Allodapini) from Vietnam, with a key to female socially parasitic Braunsapis in Asia - Packer, Laurence (Journal of Melittology, 2018)
Braunsapis scorpius Packer, new species, from Vietnam, is diagnosed, described, and illustrated. In addition to adaptations commonly associated with related social parasites (i.e., reduced metatibial hairs, short mouthparts, and absence of a basitibial plate), it has a remarkably recurved metasomal apex. It is compared to other socially parasitic members of its genus from Asia and a key to females of these social parasites is provided.